Repurposing macitentan with nanoparticle modulates tumor microenvironment to potentiate immune checkpoint blockade. (September 2021) - Son, Soyoung; Shin, Jung Min; Shin, Sol; Kim, Chan Ho; Lee, Jae Ah; Ko, Hyewon; Lee, Eun Sook; Jung, Jae Min; Kim, Jeongyun; Park, Jae Hyung
Abstract: Immune checkpoint therapy (ICT), which reinvigorates cytotoxic T cells, provides clinical benefits as an alternative to conventional cancer therapies. However, its clinical response rate is too low to treat an immune-excluded tumor, owing to the presence of abundant stromal elements impeding the penetration of immune cells. Here, we report that macitentan, a dual endothelin receptor antagonist approved by the FDA to treat pulmonary arterial hypertension, can be repositioned to modulate the desmoplastic tumor microenvironment (TME). In the 4T1 orthotopic tumor model, the polymeric nanoparticles bearing macitentan (M-NPs) prevent fibrotic progression by regulating the function of cancer-associated fibroblasts, attenuate the biogenesis of cancer cell-derived exosomes, and modulate the T cell subsets and distribution in TME. These results demonstrate that the M-NPs effectively reorganize the immunosuppressive TME by targeting the endothelin-1 axis and consequently exhibit synergistic antitumor effects in combination with ICT.